(untitled) (Journal of Hama University, 2019)
The aim of this study was to know the effect of high temperature during the summer and low in the winter on some race horse’s blood biochemical compounds. Where the number of all experimental animals were (44) heads of race horses, including (21) heads used in the summer and (23) heads used in the winter, and blood samples were collected from the jugular vein of all horses on the rate of a sample every two weeks during each Season, and then measured the concentration of each Glucose, cholesterol, triglycerides, calcium, total protein, phosphorus, magnesium and uric acid. The results showed that the high temperature during the summer resulted in high blood glucose and total protein concentration and decreased concentration of magnesium but did not affect concentrations of (calcium, phosphorus, cholesterol and triglycerides). While the low winter temperatures led to a high concentration of triglycerides and decreased concentration of (glucose, calcium, phosphorus, total protein and uric acid). The concentration of cholesterol and magnesium was not affected during the winter. Thus, the thermal changes led to disorder in the level of some race horse’s blood biochemical compounds.